Staphylococcus pseudoxylosus sp. nov., isolated from bovine mastitis. Issue 8 (21st June 2019) - MacFadyen, A. C.; Leroy, S.; Harrison, E. M.; Parkhill, J.; Holmes, M. A.; Paterson, G. K.
Abstract : Strain S04009 T, a Gram-stain-positive, coagulase-negative staphylococcus, was isolated from bovine mastitis in France. 16S rRNA gene analysis revealed it to be closely related to the coagulase-negative species Staphylococcus xylosus, Staphylococcus saprophyticus, Staphylococcus caeli and Staphylococcus edaphicus . At the whole-genome level, strain S04009 T had an average nucleotide identity value <95 % and an inferred DNA–DNA hybridization value <70 % when compared to these species. Furthermore, phenotypic characteristics distinguished S04009 T from those species. From these related species only strain S04009 T and S. xylosus are able to ferment xylose and these two can be distinguished by the inability of strain S04009 T to express urease activity. Based on the genotypic and phenotypic results, it is proposed that this isolate is a novel species, with the name Staphylococcus pseudoxylosus sp. nov. The type strain is S04009 T (=DSM 107950 T =CCUG 72763 T =NCTC 14184 T ).